2018
DOI: 10.1016/j.clim.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

CVID enteropathy is characterized by exceeding low mucosal IgA levels and interferon-driven inflammation possibly related to the presence of a pathobiont

Abstract: Common variable immunodeficiency (CVID), the most common symptomatic primary antibody deficiency, is accompanied in some patients by a duodenal inflammation and malabsorption syndrome known as CVID enteropathy (E-CVID).The goal of this study was to investigate the immunological abnormalities in CVID patients that lead to enteropathy as well as the contribution of intestinal microbiota to this process.We found that, in contrast to noE-CVID patients (without enteropathy), E-CVID patients have exceedingly low lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 51 publications
4
69
2
1
Order By: Relevance
“…Concurrent evidence of other viral pathogens such as parechovirus together with norovirus has also been reported in patients with “CVID enteropathy.” Conversely, one study investigating enteropathy in CVID found no evidence in norovirus in stool or biopsy samples in a patient with villous atrophy or a further 31 with evidence of increased intraepithelial leucocytes but no evidence of villous atrophy . A recent study on CVID enteropathy found low levels of norovirus in biopsies of some patients but also identified enteropathy patients without norovirus . The authors of this study implicate a bacterial pathogen instead.…”
Section: Noroviruscontrasting
confidence: 53%
“…Concurrent evidence of other viral pathogens such as parechovirus together with norovirus has also been reported in patients with “CVID enteropathy.” Conversely, one study investigating enteropathy in CVID found no evidence in norovirus in stool or biopsy samples in a patient with villous atrophy or a further 31 with evidence of increased intraepithelial leucocytes but no evidence of villous atrophy . A recent study on CVID enteropathy found low levels of norovirus in biopsies of some patients but also identified enteropathy patients without norovirus . The authors of this study implicate a bacterial pathogen instead.…”
Section: Noroviruscontrasting
confidence: 53%
“…These patients also had increased occurrence of certain bacteria (ie, Acinetobacter baumannii) in the duodenal microbial community that induced an inflammatory phenotype in macrophages. 7 These findings further support a role of IgA in CVID and a possible link to systemic inflammation. The present data shed new light on the impact of IgA on the gut microbiota composition in humans.…”
Section: Selective Iga Deficiency In Humans Is Associated With Reducementioning
confidence: 54%
“…This is in keeping with the characterization of some commensal bacteria as "pathobionts," which are commensals with the propensity to induce pathological conditions in certain situations, but are otherwise symbionts. 46 Here, two of the Gram-negative commensals tested (P. stercorea and A. junii) reside within genera of bacteria that are reported to contain pathobionts, 47,48 and thus members of these genera may induce inflammation in the setting of epithelial barrier damage. Interestingly, we have previously shown that these exact species can also induce IL-22 production by human colonic ILC3s, 49 which is a cytokine with a role in epithelial barrier maintenance and regulation of intestinal health.…”
Section: Discussionmentioning
confidence: 99%